2017
DOI: 10.1002/chem.201701164
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Long‐Chain Fatty Acids Are Preferred Ferritin Ligands That Enhance Iron Biomineralization

Abstract: Ferritin is a ubiquitous nanocage protein, which can accommodate up to thousands of iron atoms inside its cavity. Aside from its iron storage function, a new role as a fatty acid binder has been proposed for this protein. The interaction of apo horse spleen ferritin (HoSF) with a variety of lipids has been here investigated through NMR spectroscopic ligand-based experiments, to provide new insights into the mechanism of ferritin-lipid interactions, and the link with iron mineralization. 1D H, diffusion (DOSY) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Further studies regarding the whole FA profile are encouraged. On the other hand, although we had data on fatty acid concentrations in plasma rather than red blood cells, we consider that our results are not affected because it has been shown that fatty acid concentrations in plasma and red blood cells are highly correlated [61][62][63] and studies that use both biochemical parameters obtained similar results [15]. Finally, we were unable to evaluate other environmental and genetic factors that might impact on serum fatty acid concentrations during pregnancy.…”
Section: Discussionmentioning
confidence: 73%
“…Further studies regarding the whole FA profile are encouraged. On the other hand, although we had data on fatty acid concentrations in plasma rather than red blood cells, we consider that our results are not affected because it has been shown that fatty acid concentrations in plasma and red blood cells are highly correlated [61][62][63] and studies that use both biochemical parameters obtained similar results [15]. Finally, we were unable to evaluate other environmental and genetic factors that might impact on serum fatty acid concentrations during pregnancy.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, our study is a secondary analysis of a clinical trial of iron supplementation. In this sense, a physiological relationship between iron and fatty acids is hypostatized since, for instance, ferritin may incorporate FA in its structure in addition to iron [ 41 , 42 ]. However, our results did not show that the iron dosage of the supplementation had any effect on FA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium arachidonate, ARA, was prepared by adding H 2 O (fluxed with nitrogen) directly to the vial obtained from the manufacturer to a concentration of 15 mM [63]. The solution was aliquoted in Wheaton glass serum bottles (Z113948) in 200-500 µL and clamped under nitrogen in a glovebox.…”
Section: Fatty Acid Samples Preparationmentioning
confidence: 99%